Virtual reality spine surgery simulation: an empirical study of its usefulness. (November 2014) - Gasco, Jaime; Patel, Achal; Ortega-Barnett, Juan; Branch, Daniel; Desai, Sohum; Kuo, Yong Fan; Luciano, Cristian; Rizzi, Silvio; Kania, Patrick; Matuyauskas, Martin; Banerjee, Pat; Roitberg, Ben Z.
<x content-type="archive" xml:space="preserve">Abstract</x> Objective: This study explores the usefulness of virtual simulation training for learning to place pedicle screws in the lumbar spine. Methods: Twenty-six senior medical students anonymously participated and were randomized into two groups (A = no simulation; B = simulation). Both groups were given 15 minutes to place two pedicle screws in a sawbones model. Students in Group A underwent traditional visual/verbal instruction whereas students in Group B underwent training on pedicle screw placement in the ImmersiveTouch® simulator. The students in both groups then placed two pedicle screws each in a lumbar sawbones models that underwent triplanar thin slice computerized tomography and subsequent analysis based on coronal entry point, axial and sagittal deviations, length error, and pedicle breach. The average number of errors per screw was calculated for each group. Semi-parametric regression analysis for clustered data was used with generalized estimating equations accommodating a negative binomial distribution to determine any statistical difference of significance. Results: A total of 52 pedicle screws were analyzed. The reduction in the average number of errors per screw after a single session of simulation training was 53·7% (P = 0·0067). The average number of errors per screw in the simulation group was 0·96 versus 2·08 in the non-simulation group. The simulation group outperformed the non-simulation group in all variables measured. The three most benefited measured variables were length error (86·7%), coronal error (71·4%), and pedicle breach (66·7%). Conclusions: Computer-based simulation appears to be a valuable teaching tool for non-experts in a highly technical procedural task such as pedicle screw placement that involves sequential learning, depth perception, and understanding triplanar anatomy.